University social responsibility: The role of teachers - Viviane de Moraes Abrah\~ao; María Vaquero-Diego; Rosa Currás Móstoles (Journal of Innovation & Knowledge (JIK), 2024)
In the last decades, the social impact of universities has arisen as a new concern, which has shifted the way academic knowledge is designed to include topics such as inclusion, environmental protection, ethics, and so on. Being teachers the main actors of these changes, it is necessary to understand their beliefs and practices regarding this matter. This study aims to analyze the perception and curricular practices of higher education teachers of business-related subjects regarding University Social Responsibility (USR). A sample of twenty-one university teachers related to socially relevant subjects in business degrees was selected to answer a questionnaire about their perceptions and practices regarding USR. In general, the findings indicate that teachers are not fully aware of the role of social topics in their subjects, and do not engage their students in these matters within their subjects. In addition, teachers do not fully perceive actions of social responsibility taken by the university. This diagnostic study may enable future changes in curricular practices and teacher training that will allow students to receive a complete education about social issues related to their professional development.
Keywords: I23; M14; O35; D63; A22; 650; University social responsibility; Higher education; Social justice; Teacher's practices; Classification codes